Utility Privatization and Regulation 2003
DOI: 10.4337/9781781951316.00013
|View full text |Cite
|
Sign up to set email alerts
|

Consumer participation and pro-poor regulation in Latin America

Abstract: In spite of not being 'public goods' in the strict sense of the term, public provision has been a common way of supplying utilities services around the world. Among the major reasons underlying the dominant position of the public sector as the provider of infrastructure are the recognition of the economic and political importance of infrastructure for development, and the faith that government provision could offset market failures characterizing the utilities market. However, under public provision, universal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…"Asia's governments rely too much on under-equipped and unsupported independent regulators to carry out tasks that are beyond their capabilities" (Jacobs, 2004: 4). In Latin America there is often a lack of political support for independent regulation and a lack of commitment to maintaining regulatory independence (Ugaz, 2003). In the context of Africa, it was found that "regulation is being examined as part of individual sector initiatives, but these efforts are uncoordinated, and implementation is being left to follow privatization instead of being put in place concurrently" (Campbell-White and Bhatia, 1998: 5).…”
Section: (B) Regulatory Quality and Development Outcomesmentioning
confidence: 99%
“…"Asia's governments rely too much on under-equipped and unsupported independent regulators to carry out tasks that are beyond their capabilities" (Jacobs, 2004: 4). In Latin America there is often a lack of political support for independent regulation and a lack of commitment to maintaining regulatory independence (Ugaz, 2003). In the context of Africa, it was found that "regulation is being examined as part of individual sector initiatives, but these efforts are uncoordinated, and implementation is being left to follow privatization instead of being put in place concurrently" (Campbell-White and Bhatia, 1998: 5).…”
Section: (B) Regulatory Quality and Development Outcomesmentioning
confidence: 99%
“…Published between 1995 and 2005, these studies evaluated the effects of privatizations in Latin America that occurred between 1989 and 2000. We summarize other studies not of a strictly comparative nature in Table 2 (13)(14)(15)(16)(17). Next, to elucidate further the challenges of water privatization, we briefly examine the experiences of three cities in Bolivia: Cochabamba, El Alto, and La Paz.…”
Section: Methodsmentioning
confidence: 99%
“…The request for a substantial rate increase follows heavy losses that the company suffered from Argentina's 2002 freezing of utility rates and con-version of those rates to devalued pesos. Several studies (7,13,16) note the difficulties of implementing appropriate regulatory frameworks for protecting the public from exploitative pricing. Ugaz (16) notes that while regulation has been successful in protecting investors and achieving efficiency gains, rising utility prices cast doubt on how effectively regulation has protected poor consumers.…”
Section: Public Health Improvement: Access and The Related Issue Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, these country studies seem very sensitive to the fact that some government increased tariff before privatization. On the other hand, Ugaz (2002) remarks that privatization implied new tariff structures which was more cost-reflective. For the three countries she considers, she finds the same pattern of rebalancing: an increase in fixed charges and a decrease in variable unit prices.…”
Section: Existing Empirical Research On the Redistribution Effects Ofmentioning
confidence: 99%